Contribution of thermal energy to initial ion production in matrix‐assisted laser desorption/ionization observed with 2, 4, 6‐trihydroxyacetophenone. (18th June 2014) - Lai, Yin‐Hung; Chen, Bo‐Gaun; Lee, Yuan Tseh; Wang, Yi‐Sheng; Lin, Sheng Hsien
<x xml:space="preserve">Abstract</x> RATIONALE Although several reaction models have been proposed in the literature to explain matrix‐assisted laser desorption/ionization (MALDI), further study is still necessary to explore the important ionization pathways that occur under the high‐temperature environment of MALDI. 2, 4, 6‐Trihydroxyacetophenone (THAP) is an ideal compound for evaluating the contribution of thermal energy to an initial reaction with minimum side reactions. METHODS Desorbed neutral THAP and ions were measured using a crossed‐molecular beam machine and commercial MALDI‐TOF instrument, respectively. A quantitative model incorporating an Arrhenius‐type desorption rate derived from transition state theory was proposed. Reaction enthalpy was calculated using GAUSSIAN 03 software with dielectric effect. Additional evidence of thermal‐induced proton disproportionation was given by the indirect ionization of THAP embedded in excess fullerene molecules excited by a 450 nm laser. RESULTS The quantitative model predicted that proton disproportionation of THAP would be achieved by thermal energy converted from a commonly used single UV laser photon. The dielectric effect reduced the reaction Gibbs free energy considerably even when the dielectric constant was reduced under high‐temperature MALDI conditions. With minimum fitting parameters, observations of pure THAP and THAP mixed with fullerene both agreed with predictions. CONCLUSIONS Proton disproportionation of solid THAP was energetically favorable with a single UV laser photon. The quantitative model revealed an important initial ionization pathway induced by the abrupt heating of matrix crystals. In the matrix crystals, the dielectric effect reduced reaction Gibbs free energy under typical MALDI conditions. The result suggested that thermal energy plays an important role in the initial ionization reaction of THAP. Copyright © 2014 John Wiley & Sons, Ltd.